2019
DOI: 10.1182/bloodadvances.2018026625
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial comparing standard vs sequential high-dose chemotherapy for inducing early CR in adult AML

Abstract: Here we evaluated whether sequential high-dose chemotherapy (sHD) increased the early complete remission (CR) rate in acute myelogenous leukemia (AML) compared with standard-intensity idarubicin-cytarabine-etoposide (ICE) chemotherapy. This study enrolled 574 patients (age, 16-73 years; median, 52 years) who were randomly assigned to ICE (n = 286 evaluable) or sHD (2 weekly 3-day blocks with cytarabine 2 g/m2 twice a day for 2 days plus idarubicin; n = 286 evaluable). Responsive patients were risk-stratified f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 59 publications
1
37
0
Order By: Relevance
“…In this context, the purpose of this study was to define the association of molecular mutations with the outcome of a cohort of 221 NK-AML patients treated according to a prospective trial comparing a standard vs. high-dose chemotherapy regimen for remission induction (ClinicalTrials.gov identifier: NCT00495287) [12].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the purpose of this study was to define the association of molecular mutations with the outcome of a cohort of 221 NK-AML patients treated according to a prospective trial comparing a standard vs. high-dose chemotherapy regimen for remission induction (ClinicalTrials.gov identifier: NCT00495287) [12].…”
Section: Introductionmentioning
confidence: 99%
“…Complete remission (CR), non‐responsive disease (NR), early induction death (ED), disease‐free survival (DFS), and overall survival (OS) were defined according to standard criteria 27 . For risk definition, patients were stratified according to the original NILG study design 26 and the European Leukemia Net (ELN) 2010 system in post hoc analysis 28 …”
Section: Methodsmentioning
confidence: 99%
“…The NILG-AML 02/06 multicentric Italian trial (17) enrolled 574 patients with newly diagnosed AML [≥20% bone marrow (BM) blasts] or high-risk MDS (10)(11)(12)(13)(14)(15)(16)(17)(18)(19) between 2007 and 2012. All participants were randomized to receive induction with standard-dose idarubicin, cytarabine and etoposide (ICE) or high-dose cytarabine and idarubicin (sHD).…”
Section: Patients Treatment Cytogenetic and Molecular Analysesmentioning
confidence: 99%
“…Patients not responding to first induction underwent an intensified re-induction with sHD. A consolidative alloHSCT was performed in highrisk patients based on study-specific risk stratification, as previously reported (17). Written informed consent for inclusion in the clinical trial and genetic analyses was provided by all patients.…”
Section: Patients Treatment Cytogenetic and Molecular Analysesmentioning
confidence: 99%
See 1 more Smart Citation